Pulsed flow and time-resolved dielectric spectroscopy of electrorheological fluids - Rattray, P. (Cranfield University, 1994)
Research has been undertaken into the dielectric and rheological properties of electrorheological (ER) fluids. The fluids studied were based on acene-quinone radical polymers made within the department dispersed in silicone oil. A commercial poly(1ithium methacrylate) dispersion was also examined. As a means of probing the underlying mechanisms of the E phenomenon, the permittivity of the fluids was measured from 12 Hz to 100 kHz under both static and dynamic conditions. Results indicated that a interfacial polarization process was taking place. A series of visual observations were made of fluids under different fielding patterns. A series of photographs were taken that illustrated the structure formation with elapsed time in a dilute fluid. Also photographs were taken of the final structure formed under different field conditions. .. To perform permittivity measurements of the fluid when a electric field was applied, a high voltage biasing unit was designed, built and proved. This allowed the application of a continuous DC electric field of up to 3 kVmm" and the permittivity to be measured from 150 H t 100 kl-Iz. Through a series of experiments it was found that the low frequency permittivity increased with increasing electric field. This result was partially explained by the Sillars model. The fluids were also subjected to shear rates from 1500 to 60 s". Flow modified permittivity resonances were found at the predicted frequencies. However, the resonant frequency did not move significantly under the application of a electric field. The structuring process was time resolved and a model was made to predict the sealing of the characteristic structuring time. The rheological response of the fluids when subjected t pulsed DC fields was examined and found to be dominated by a instrumentational effect. Al experimental procedures are given along with a comprehensive examination of the equipment. The results are discussed as they occur in terms of the models appropriate to that particular event.